2019
DOI: 10.12659/msm.916313
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3 Prevents Epithelial-Mesenchymal Transition of HMrSV5 Human Peritoneal Mesothelial Cells by Inhibiting Histone Deacetylase 3 (HDAC3) and Increasing Vitamin D Receptor (VDR) Expression Through the Wnt/β-Catenin Signaling Pathway

Abstract: Background Peritoneal dialysis is the most common treatment for end-stage renal disease. However, peritoneal fibrosis resulting from long-term peritoneal dialysis restricts peritoneal ultrafiltration. Previous studies have shown a role for 1,25-dihydroxyvitamin D3 (1,25[OH] 2 D3) in preventing fibrosis, but the potential mechanisms remain unknown. This study aimed to investigate the role of 1,25(OH) 2 D3 in epithelial-mesenchymal transition (EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The present study analyzed Vdr expression in human PTc and normal thyroid follicular cells, and revealed that Vdr mrna and protein expression levels were increased in PTc cells compared with thyroid follicular cells, which was consistent with previous studies (20,31). Previous studies had revealed that Vdr has the potential to regulate cancer cellular activities and influence tumor progression and metabolism by binding to vitamin d (15,20,32,33). For example, in vitamin d-treated breast cancer cells, silencing of Vdr promotes cancer cell motility and invasiveness by increasing the expression of proteins involved in cell adhesion, proliferation, cytoskeletal organization (33).…”
Section: Effect Of Vitamin D and Kd-vdr On Cell Invasion To Elucidatsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study analyzed Vdr expression in human PTc and normal thyroid follicular cells, and revealed that Vdr mrna and protein expression levels were increased in PTc cells compared with thyroid follicular cells, which was consistent with previous studies (20,31). Previous studies had revealed that Vdr has the potential to regulate cancer cellular activities and influence tumor progression and metabolism by binding to vitamin d (15,20,32,33). For example, in vitamin d-treated breast cancer cells, silencing of Vdr promotes cancer cell motility and invasiveness by increasing the expression of proteins involved in cell adhesion, proliferation, cytoskeletal organization (33).…”
Section: Effect Of Vitamin D and Kd-vdr On Cell Invasion To Elucidatsupporting
confidence: 91%
“…Previous studies had revealed that VDR has the potential to regulate cancer cellular activities and influence tumor progression and metabolism by binding to vitamin D ( 15 , 20 , 32 , 33 ). For example, in vitamin D-treated breast cancer cells, silencing of VDR promotes cancer cell motility and invasiveness by increasing the expression of proteins involved in cell adhesion, proliferation, cytoskeletal organization ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VDR is present mainly in metabolic tissues, but also in almost all human cell types ( 10 ); furthermore, VDR expression is low in normal cells, increases in malignant cells and is reduced with tumor growth ( 5 , 11 ). VDR is also expressed in human and rodent peritoneal mesothelial cells and human bronchial epithelial cells ( 12 15 ); however, the presence of VDR in pleural mesothelial cells has yet to be demonstrated. Studies have recently indicated that calcitriol reduces fibrosis and prevents epithelial-mesenchymal transition in human peritoneal mesothelial cells in vitro ( 12 , 14 ), while vitamin D analogs reduce peritoneal fibrosis in vivo ( 15 ) through antinflammatory mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…VDR is also expressed in human and rodent peritoneal mesothelial cells and human bronchial epithelial cells ( 12 15 ); however, the presence of VDR in pleural mesothelial cells has yet to be demonstrated. Studies have recently indicated that calcitriol reduces fibrosis and prevents epithelial-mesenchymal transition in human peritoneal mesothelial cells in vitro ( 12 , 14 ), while vitamin D analogs reduce peritoneal fibrosis in vivo ( 15 ) through antinflammatory mechanisms. In addition to its nuclear localization, VDR has been recently localized in mitochondria and calcitriol was found to suppress mitochondrial respiration in cancer cell lines, keratinocytes and adipocytes, affecting both cell growth and differentiation, as well as lipid metabolism ( 16 19 ).…”
Section: Introductionmentioning
confidence: 99%